SUPPLY CHAIN TRACKABILITY SYSTEM FOR FOOD SAFETY OF HALAL PRODUCTS BASED ON HACCP AND SCOR METHODS (Case Study on Aitamie Non-Gluten Dry Noodle Products) - Wita Nuradiani; Kuncorosidi Kuncorosidi (STIESA Press, 2021)
This study aims to determine the traceability and security systems that exist in the product supply chain for Youngsters SMEs, as well as to find out how the traceability system in the supply chain for food safety for halal products in companies uses the HACCP and SCOR methods. The method used is Hazard Analysis Critical Control Point (HACCP) and Supply Chain Operation Reference (SCOR) with weighting using the AHP method. The results showed that there were 4 stages of the process which were critical points, namely, the process of steaming the dough, molding the dough, drying and packaging. Therefore, it is necessary to record the steaming time which is monitored by the production department, keep the dough not too wide, only using one heater with an initial temperature of 55ºC and 45ºC for the blower on the extruder machine to prevent overheating, for the drying process, it is necessary to do 2 stages. drying process, using a waring cloth as a tray cover when drying outside the room, and periodically checking the tray position. For the packaging process, corrective action takes the form of using silica gel and manually minimizing the air space in the package. The results of measuring slot deposit 5000 supply chain performance using the SCOR method show that the greatest weight is the responsiveness dimension, which means that for SMEs the most important thing in the SME supply chain is responsiveness, of the 45 KPIs there are 32 validated KPIs. Overall, the supply chain performance value is 75.30, which means it is in the good or good category. However, of the 32 KPIs, it is known that there are 11 KPIs that require improvements with average and marginal performance, namely, Perfect order fulfillment (POF), Delivery performance to customer commit day, Order fulfillment cycle time, Source cycle time, Fillrate by line item, Supply Source chain flexibility and adaptability, Currenton hand inventory, forecast accuracy, make flexibility, Cost to make, cash to cash cycle time.